(untitled) (Research, Society and Development, 2022)
Objective: To understand the main neurological manifestations of cerebral malaria in Brazil. Methodology: This is an integrative review that searched literature between the years 2007 to 2022, through the descriptors “malaria”, “diseases of the nervous system” and “Brazil”, researched on LILACS, PUBMED and SciELO platforms. Publications with full text available, published between 2007 and 2022, in English, Portuguese and Spanish were used. In addition, studies that did not address the research proposal, as well as repeated or duplicated studies were excluded. Results: The neurological manifestations most frequently reported in the studies presented are characterized by cerebral edema, seizures, coma, cognitive deficit, hippocampal impairment and disturbance of consciousness. Furthermore, the clinical signs and symptoms of severity differ in adults and children, and in both cases they can configure the lethal form of the pathology. Conclusion: The main neurological manifestations of the disease involve coma, seizures, changes in muscle tone, loss of reflexes, and unspecified behavioral and motor dysfunctions. Despite the neurological clinical signs and symptoms found, cerebral malaria is still a neglected disease, with differences in prognosis between child and adult age groups.